Dinamika Hubungan Politik dan Pendidikan Agama di Kampus: antara Keseimbangan dan Konflik - Ali Nurdin; Eneng Humaeroh (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Politics and religion have a close relationship and are important subjects in social and political studies. This research presents an analysis of the dynamics of the relationship between religious education on campus and politics in the context of contemporary dynamics. This research focuses on the role of religion in the formation of public policy, political identity, and the dynamics of social conflict. This research study is a discourse or literature search, to find out the relationship between these two problems. This research pays attention to phenomena and changes in power dynamics, transformation of religious identity, and ideological conflicts involving religion as a central aspect. This article also considers the implications of the interaction between religion and politics for democracy. The research method used is a qualitative approach. The data sources used are a combination of educational and religious political perspectives. Literature is used to explain how religion is often a source of inspiration for political movements, both in practical contexts and as a basis for thought. The analysis of this research aims to encourage a broader and deeper dialogue about how society, especially educational institutions, can manage and understand the role of religion in a democratic and inclusive political space.